MEMAHAMI PENYEBAB KEBAKARAN HUTAN DAN LAHAN SERTA UPAYA PENANGGULANGANNYA: KASUS DI PROVINSI KALIMANTAN BARAT - SAHAT M. PASARIBU; SUPENA FRIYATNO (SOCA: Jurnal Sosial Ekonomi Pertanian, 2008)
Land and forest fire have grabbed much concern and been considered as national issue. Theevent occurs repeatedly year by year, specifically in Sumatra and Kalimantan islands.Government institutions and local community, including farmers and estate enterprises have avery close linkage in such disaster. The smoke produced by the fire has been transformed intoa widespread of thick cloud and immediately affects health conditions of the community. Thesmoke also directly interfere river, land, and air transport systems, thus influencing basicsocio-economic life of human being. This paper is aimed at understanding about how forestfire occurs and its effect on agricultural sector. With rapid rural appraisal method, this papereventually comes to main results and findings as follows: (a) elaboration of five identifiedtypologies of land and forest fire, (b) analysis of direct and indirect impacts of the fire onagricultural sector, (c) identification of who and why land and forest fire occur, and (d)recommendation of programs to persuasively eliminate land and forest fire. Many partieshave its own share and proportion to contribute to land and forest fire. Imbalanced-natureoccurs and causes specific disaster with environment degradation. People have manydifficulties to recover from such situation. The successful to get rid of land and forest fire isheavily depending on how alternative applied technologies can easily be adopted and lawenforcement can widely be implemented.